O Catolicismo nos contextos e crcunstâncias da modernidade em Cabo Verde - Adilson Filomeno Carvalho Semedo (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
This paper focus on the opposition between religion and social modernization and highlights the role of Catholicism in the contexts and circumstances of Cape Verdean modernity construction, derived process in the functional differentiation and complexity of the relations between political and religious subsystems of society